Otic Langerhans' Cell Histiocytosis in an Adult: A Case Report and Review of the Literature - Gungadeen, Anil (Hindawi Publishing Corporation, 2013)
Objective. To present a case of otic Langerhans' cell histiocytosis in an adult. Also included the diagnosis and management of the condition and a review of the relevant literature. Case Report. We report a case of a 41-year-old man with a history of persistent unilateral ear discharge associated with an aural polyp. Radiological imaging showed bony lesions of the skull and a soft-tissue mass within the middle ear. Histological analysis of the polyp demonstrated Langerhans' cell histiocytosis. His otological symptoms were completely resolved with the systemic therapy. Conclusions. Otic Langerhans' cell histiocytosis can present in adults. Persistent ear symptoms along with evidence of soft-tissue masses within the ear and bony lesions of the skull or elsewhere should prompt the otolaryngologists to include Langerhans' cell histiocytosis in their differential diagnosis. Management should be with systemic therapy rather than local surgical treatment.